2020
DOI: 10.1080/17524032.2020.1736116
|View full text |Cite
|
Sign up to set email alerts
|

“We are a Bit Blind About it”: A Qualitative Analysis of Climate Change-Related Perceptions and Communication Across South African Communities

Abstract: Climate change-related perceptions and communication are important factors influencing people's support for climate change policies and individual behavior. Since research on both climate change-related perceptions and communication is biased towards Western countries and standardized research methodologies, this paper investigates perceptions across South African communities using a deductive-inductive qualitative approach. 20 individuals in three communities of a South African town were interviewed about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…In line with this, both the distribution of answers between the six categories and the content of the specific impacts could be different. For example, one study among people from the Western Cape in South Africa found that most interviewees mentioned the area’s ongoing water scarcity and rising food prices as effects of climate change [ 37 ], while another study found that air quality was frequently associated with climate change concern among residents in China [ 3 ]. Further, since previous research has shown that climate change impacts and impact associations can differ between regions within a country [ 38 ], future research could either zoom out to different parts of the world and/or zoom in to different regions within a country.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, both the distribution of answers between the six categories and the content of the specific impacts could be different. For example, one study among people from the Western Cape in South Africa found that most interviewees mentioned the area’s ongoing water scarcity and rising food prices as effects of climate change [ 37 ], while another study found that air quality was frequently associated with climate change concern among residents in China [ 3 ]. Further, since previous research has shown that climate change impacts and impact associations can differ between regions within a country [ 38 ], future research could either zoom out to different parts of the world and/or zoom in to different regions within a country.…”
Section: Discussionmentioning
confidence: 99%
“…The media's role in climate change communication is crucial because of its ability to reach vast numbers of people and being a "definer of reality" (Evans & Musvipwa, 2016, p. 199). On the other hand, public perceptions of climate change tend to be intertwined with media representations of the phenomenon (Mahl et al, 2020). Thus, researchers have usually gauged public perception of climate change by studying media reports on the issue.…”
Section: Background Climate Journalism In South Africamentioning
confidence: 99%
“…While it is scientifically challenging to attribute any one extreme weather event to climate change (van Aalst, 2006 ), personal experience of extreme events has been documented to increase climate change risk perceptions by invoking a concrete understanding of the effects of climate change in reality (Akerlof et al., 2013 ; Demski, Capstick, Pidgeon, Sposato, & Spence, 2017 ; Reser, Bradley, & Ellul, 2014 ). There is a growing body of evidence that suggests a belief, within Africa, that extreme and erratic weather events are increasing, primarily as a result of climate change (Ayal & Leal Filho, 2017 ; Ayanlade, Radeny, & Morton, 2017 ; Mahl, Guenther, Schäfer, Meyer, & Siegen, 2020 ; Sutcliffe, Dougill, & Quinn, 2016 ). These events, in east Africa, include increased average temperatures, decreased and/or more variable precipitation resulting in heavy rainfall events and flooding, a shorter or delayed rainy season, and longer dry spells and droughts (Chepkoech, Mungai, Stöber, Bett, & Lotze‐Campen, 2018 ; Egeru, 2016 ; Gross‐Camp, Few, & Martin, 2015 ; Mubiru et al., 2018 ).…”
Section: Exploring Climate Change Risk Perceptions and Their Determin...mentioning
confidence: 99%